Study of Cosmic Radiation Near the Earth's North Geomagnetic Pole. - Pomerantz,Martin A (1976)
The nucleonic intensity observations at Thule, Greenland have established an apparently longer data base than any other station in either polar cap. During the brief period covered by this report, significant progress has been made toward understanding three important phenomena: (1) the origin of transient cosmic ray intensity variation; and (2) the mechanism that is responsible for producing north-south anisotropy and acceleration of relativistic cosmic rays between converging interplanetary shock waves. These results are described in detail. (Author) Continuation of Contract AF 19(628)-5200.